Controlling odour emissions in poultry production through dietary interventions: prospects and challenges - Adamu, Garba; Hassim, Hasliza Abu; Kumar, Pavan; Sazili, Awis Qurni; Mohd Zainudin, Mohd Huzairi (Taylor and Francis, 2024)
The present intensive rearing of poultry with high bird density leads to the emission of harmful greenhouse gases, hydrogen sulphide and volatile organic compounds emanating unpleasant odours. These compounds pose risks to animals’ and workers’ health. Prolonged exposure to these harmful gases can lead to respiratory and chronic diseases. Among various strategies, dietary interventions could be a promising methodology to mitigate odour emission from poultry farms by improving digestibility, efficient nutrient utilisation and controlling microbial decomposition of manure. Various feed additives increase the nutrient’s digestibility and improve gut health, leading to fewer nutrients remaining in the manure for microbial decomposition. Recently, various enzymes such as non-starch polysaccharides, phytases and proteases have been used in improving the digestibility and nutrient utilisation efficiency of feed by cleaving the complex structures. The application of appropriate additives could reduce the odour emanating from poultry farms, consequently improving the sustainability of poultry production and savings on the application of various filtration and adsorption technologies. This present paper critically reviewed the various aspects of dietary interventions in managing odour emissions from poultry farms.